Comparison of the Impact of Atracurium and Cisatracurium on the Neutrophil-To-Lymphocyte Ratio in Addition to Hemodynamic Changes during Anesthesia Induction - Behzad Nazemroaya; Sahand Taei (Archives of Anesthesia and Critical Care)
Background: Muscle relaxants are used for two general purposes. One is to ease endotracheal intubation, and the other is provide surgical relaxation. This study has been designed with the aim of assessing the impact of atracurium and cisatracurium on patients at the anesthesia induction and the neutrophil to lymphocyte ratio. Methods: This is a randomized clinical trial that was performed in 2022-2023 in Kashani hospital in Isfahan, Iran on patients that were candidates for elective surgery under general anesthesia by atracurium or cisatracurium. A total number of 80 patients entered and were randomized into two group’s one receiving group atracurium 0.5mg/kg, and other group received cisatracurium 0.15mg/kg over 60 seconds as NMB. Blood sample were taken base time, after 3, and 20 minutes following intubation. Qualitative data is reported as frequency with percentage. And quantitative data as average with standard deviation. Statistical analysis was done using SPSS version 25. Qualitative data were analyzed using chi-square tests and quantitative data using independent T test. Significance level was defined as p value <0.05. Results: Overall, 80 patients were enrolled in this study. 40 of them belonged to the cisatracurium group and 40 to the atracurium group. Average age of the participants was 42.86 (±14.52) years old. Mean arterial pressure (MAP) in cisatracurium group dropped significantly following intubation (p<0.005), while it rose significantly in the atracurium group (p<0.05). However neutrophil to lymphocyte ratio (NLR) was significantly higher in the cisatracurium group following intubation (P<0.05). Conclusion: While the use of atracurium in patients is still safe, is yet more correlated with pronounced hemodynamic instability compared to cisatracurium.